Neonatal, Infant and Under-Five Mortality: an Application of Cox Proportional Hazard Model to Bdhs Data (Journal of the Asiatic Society of Bangladesh, Science, 2018)
This study utilizes data derived from the Bangladesh demographic and health survey (BDHS), 2014 to identify the determinants of neonatal, infant and under-five mortality in Bangladesh. Log-rank test has been used for bivariate analysis. Regression analysis has been performed by applying Cox proportional hazard model to the data. It has been found from the analysis that maternal education, region, exposure to NGO activities are significant determinants of under-five and infant mortality whereas region, gender of child, child’s size at birth play significant role in reducing neonatal mortality in Bangladesh. The findings of the study suggest that policymakers should give priority on maternal education, region, and child’s size at birth as well as exposure to NGO activities to reduce neonatal, infant and under-five mortality in Bangladesh.Asiat. Soc. Bangladesh, Sci. 44(1): 7-14, June 2018